Chebyshev differentiation matrices for efficient computation of the eigenvalues of fourth-order Sturm–Liouville problems - Saleh Taher, A.H.; Malek, A.; Momeni-Masuleh, S.H. (Applied mathematical modelling, 2013)
In this paper, an efficient technique based on the Chebyshev spectral collocation method for computing the eigenvalues of fourth-order Sturm–Liouville boundary value problems is proposed. The excellent performance of this scheme is illustrated through four examples. Numerical results and comparison with other methods are presented.